SECONDARY STUDENTS’ COVARIATIONAL REASONING IN SOLVING THE FILLING BOTTLE PROBLEM - Annisa, Fitri; Sudirman, Sudirman; Kusumasari, Vita (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Covariational reasoning is closely related to the concept of functions, as both involve relationships between two quantities. Although it is useful for understanding change and interdependence between quantities, the notion of covariation is rarely introduced directly to students since it is not explicitly included in the school curriculum. This study aims to explore students’ covariational reasoning in constructing function graphs in the context of a filling bottle problem. Three aspects of covariational reasoning were analyzed: identifying variables, ways of coordinating variables, and quantifying the rate of change. This qualitative research employed a case study design and involved three 11th-grade students selected through purposive sampling. Data were obtained from students’ responses to the filling bottle task and interviews, and analyzed through data condensation, data display, and conclusion drawing. The findings indicate that (1) students had difficulty identifying the independent and dependent variables in a functional problem, especially graph, (2) students tended to rely on secondary variables when coordinating the independent and dependent variables, and (3) students’ ability to quantify the rate of change depended on their ability to identify and coordinate the two variables.